Gestión de crédito y cobranza y su incidencia en la recuperación de cartera con plan alternativo y manual de procedimiento para la cobranza en el almacén innova en el cantón La Maná provincia de Cotopaxi en el período 2013 - Calvopiña Ormaza, Merlin Patricia (2015)
This research raises: the topic of the Management Credit and Collections in recovering portfolio with Alternative Plan and Procedure Manual into Innova warehouse; located in La Maná canton, Cotopaxi Province, for it begins with a diagnosis of the problem under study, identifying the causes and effects that arise in the current field. This leads to the search for a solution, for which, establish the need of a Procedures Manual and Alternative Plan to be developed in the area of credit management, focused on meeting the goals proposed allowing that the business owner, improve his credit management in the economic activity of the business as is selling appliances.